STANDARDIZATION OF STRENGTHENING OF THE INTERNAL SURFACE OF CYLINDRICAL PARTS USING THE METHOD OF PLASTIC DEFORMATION - Husanboyev, Abdulkasim Mamajonovich (Educational Research in Universal Sciences, 2023)
Among the types of strengthening processing of details with a flat external, internal and external cylindrical surface, complex technological surface shape in mechanical engineering, the technological processes of plastic deformation are presented. The effect of plastic deformation on metals and the change in structure and increase in the strength of the detail have been theoretically studied.